Comprehensive Rehabilitation Improves Motor Function and Independence in a Patient with Left Hemiparesis Post-Ischemic Stroke: A Case Report - Tasia Irma Endriani; Elien Wihestin (HM Publisher, 2025)
Background: Stroke remains a leading cause of disability worldwide, with ischemic stroke being the predominant type. Left-sided hemiparesis resulting from ischemic stroke significantly impairs motor function and activities of daily living, necessitating comprehensive rehabilitation interventions. This case report details the journey of a 72-year-old female patient who experienced left hemiparesis due to an ischemic stroke and underwent a comprehensive rehabilitation program. Case presentation: A 72-year-old female patient presented with sudden onset weakness in her upper and lower left limbs following an ischemic stroke. Initial assessments revealed significant impairments in motor function, balance, and self-care abilities, classifying her as having a moderate disability according to the Barthel Index. The rehabilitation program included passive and active range of motion exercises, functional mobilization techniques, resistance and balance training, infrared therapy, psychological support, and patient education. Conclusion: The comprehensive rehabilitation strategy implemented in this case resulted in significant improvements in the patient's motor function, balance, confidence, and independence in performing daily activities. This case underscores the crucial role of tailored and comprehensive rehabilitation programs in enhancing recovery and improving the quality of life for individuals following an ischemic stroke.